Evaluation of the Competitiveness Model in the Steel Industry with a Technology Transfer Approach - Ali Amraei; Safieh Mehrinejad; Amir Bayattork (مدیریت صنعتی)
Objective Given the dependencies of key economic sectors, the global steel demand is expected to increase. Therefore, pursuing multiple strategies and aligning with global market developments is essential to enhance and achieve competitiveness in this industry. One of the development approaches in the steel industry, like other technology-based industries adapting to advancements in new technologies, is using a technology transfer approach. This industry is one of the largest and most important industries in the world and plays a very important role in many economic sectors. It can be significantly recognized in global markets as one of the main and powerful players by improving its competitiveness. The main objective of this research is to evaluate the competitiveness model in the steel industry with a technology transfer approach.